2014
DOI: 10.15296/ijwhr.2014.22
|View full text |Cite
|
Sign up to set email alerts
|

Maternal Satisfaction about Prenatal and Postnatal Caresin Vaginal and Cesarean Section Delivery at Teaching andNon- teaching Hospitals of Tabriz/ Iran.

Abstract: Objectives: The main goal of care services is provide and promote mankind's health. Patient satisfaction is recognized as an important parameter for assessing the quality of patient care services. Spatially mothers' satisfaction from delivery is very important because it influence on family and society psychological health. The aim of this study was comparing maternal satisfaction about prenatal and postnatal cares in vaginal and cesarean section delivery at teaching and nonteaching hospitals of Tabriz/ Iran. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 9 publications
0
3
0
Order By: Relevance
“…Furthermore, as less severe hemodynamic changes are seen with midazolam, it seems that midazolam can be a much better choice than propofol. Also,to increase the patients satisfaction which is an important factor in conscious patients undergone a surgery like cesarean section, especially in teaching hospitals which is lower than nonteaching hospitals, as presented with Nagizadeh et al ( 24 ), we can reach to this purpose with appropriate use of low doses agents with no adverse effect of drugs overdose.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, as less severe hemodynamic changes are seen with midazolam, it seems that midazolam can be a much better choice than propofol. Also,to increase the patients satisfaction which is an important factor in conscious patients undergone a surgery like cesarean section, especially in teaching hospitals which is lower than nonteaching hospitals, as presented with Nagizadeh et al ( 24 ), we can reach to this purpose with appropriate use of low doses agents with no adverse effect of drugs overdose.…”
Section: Discussionmentioning
confidence: 99%
“…The World Health Organization (WHO) considers satisfaction for dignity, and status to be an important factor to improve the health of clients, while mentioning the most important rights of patients as including the right to informed consent, information confidentiality, access to health services, and their privacy [13,14].…”
Section: Discussionmentioning
confidence: 99%
“…This problem can also bring about such disorders as sleep problems, post-traumatic stress disorder, neglecting health care, sexual disorders, and decreased desire to have children. Studies have demonstrated that changing the method of subsequent delivery is another result of dissatisfaction in the childbirth process [13]. As dissatisfaction in different stages of childbirth can entail significant complications according to the studies, the degree of dissatisfaction the present study carried out to determine Afghan immigrant and refugee women's satisfaction with maternity wards services in Iran.…”
Section: Scibasejournalsorgmentioning
confidence: 97%